2008
DOI: 10.1080/02688690701818919
|View full text |Cite
|
Sign up to set email alerts
|

Is total excision of spinal neurenteric cysts possible?

Abstract: Spinal neurenteric cysts are intradural cystic lesions. These represent a part of the spectrum of developmental anomalies. These are rare lesions. Most of the data in literature is review of case reports. This made us evaluate our results of 23 cases and review the literature. This is a retrospective study of 23 patients managed at our institute over 20 years. The slides were retrieved and histopathological features studied. Twenty patients were less than 30 years old and 21 were males. Follow-up was available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 20 publications
0
65
0
7
Order By: Relevance
“…The incidence of NEC is approximately 0.7–1.3% of all intradural spinal cord tumors [3]. It can manifest already at the 5th week of age up to 6th decade of life, with occurrence in 2nd and 3rd decades being most common.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of NEC is approximately 0.7–1.3% of all intradural spinal cord tumors [3]. It can manifest already at the 5th week of age up to 6th decade of life, with occurrence in 2nd and 3rd decades being most common.…”
Section: Discussionmentioning
confidence: 99%
“…The GTR rates for IDEM NECs in the literature range from 71% to 75%. 8,10,12 However, GTR is not feasible for intramedullary NECs. In 8 cases in the present study, the cyst wall showed no adhesion to the spinal cord, and GTR was achieved by using microsurgical techniques.…”
Section: Diagnosis and Differentiationmentioning
confidence: 99%
“…3,18,19,21,24,37,40,41 In contrast, bone anomalies were more common in extramedullary NECs. 12 Thus, the diagnosis of an isolated intramedullary NEC without concurrent malformations becomes even more challenging.…”
Section: Diagnosis and Differentiationmentioning
confidence: 99%
See 2 more Smart Citations